Perceived Enjoyment, Curiosity, and Control Competence as Predictors of Behavioral Intention in Digital Ticket Booking Services: A Study of Indonesian Generation Z - Nayla Zannata Mugni; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2026)
This study examines the determinants of Behavioral Intention to Use digital entertainment ticket booking platforms among Indonesian Generation Z by applying the Hedonic Motivation System Adoption Model (HMSAM). A quantitative causal design was employed using survey data collected in December 2025 from 122 respondents who had used online ticket booking services within the last six months. The data were analyzed using multiple linear regression in IBM SPSS, supported by instrument testing and classical assumption checks. The results show that Perceived Enjoyment, Curiosity, and Control Competence each have a positive and significant effect on Behavioral Intention. Among the predictors, Curiosity is the most dominant factor, indicating that exploratory motivation is central in shaping reuse intention for entertainment-oriented services. The model demonstrates strong explanatory power, accounting for 80.5% of the variance in Behavioral Intention. These findings confirm HMSAM’s relevance in hedonic-dominant digital contexts and suggest that platform development should prioritize features that stimulate exploration, maintain enjoyable interaction, and strengthen user control through clear navigation and transparent transaction processes.